2021
DOI: 10.3390/genes12020216
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Sudden Infant Death Syndrome—Towards a Gene Reference Resource

Abstract: Sudden infant death syndrome (SIDS) is the unexpected death of an infant under one year of age that remains unexplained after a thorough investigation. Despite SIDS remaining a diagnosis of exclusion with an unexplained etiology, it is widely accepted that SIDS can be caused by environmental and/or biological factors, with multiple underlying candidate genes. However, the lack of biomarkers raises questions as to why genetic studies on SIDS to date are unable to provide a clearer understanding of the disease e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…A common feature of all these disorders (except the short or sometimes medium chain) is fasting hypoketotic hypoglycemia [ 8 , 9 ]. Approximately 5% of sudden deaths in childhood are secondary to FAODs [ 10 ], most of which are diagnosed postmortem. With the implementation of newborn screening, the clinical presentation and its natural history have changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of all these disorders (except the short or sometimes medium chain) is fasting hypoketotic hypoglycemia [ 8 , 9 ]. Approximately 5% of sudden deaths in childhood are secondary to FAODs [ 10 ], most of which are diagnosed postmortem. With the implementation of newborn screening, the clinical presentation and its natural history have changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…SIDS/SUID risk is still likely defined by multifactorial genetic and environmental interactions [23,24]. In one of such subjects, we detected the missense mutation in PHOX2B.…”
Section: Plos Onementioning
confidence: 99%
“…Studies have shown that, compared to controls, SIDS children have more frequent significant abnormalities of both the serotonin transporter gene [17,18] and the monoamine oxidase gene [19,20], leading to decreased serotonergic receptor binding and reduced serotonin and tryptophan hydroxylase 2 levels in the brainstem with poor function of the autonomic nervous system. Moreover, alterations in genes encoding for cardiac ion channels [21,22], proteins involved in myocardial conduction [23], skeletal muscle sodium channels [24], several immune components (complement component C4, interleukin-10 promoter) [25,26], and heat shock proteins [27] have been reported. All of these findings suggest that SIDS prone children have significant differences in several body functions with poor response in front of lifethreatening conditions.…”
Section: Present Hypothesis On Sudden Infant Death Syndrome (Sids) De...mentioning
confidence: 99%